From neuron to culture – a biosemiotic perspective of the origin and evolution of the brain according to Marcello Barbieri - Kłóś, Adam (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
Marcello Barbieri is one of the leading representatives of biosemiotics. Dissatisfied with current reductionistic approach in science, he proposes a new research programme based on the idea of semiosis. According to it, life starts with the first appearance of the genetic code, and every big evolutionary step is marked with discoveries of the new organic codes that the evolving nature makes. This paper describes Beriberi’s original theory of the origin and evolution of the brain and parallel evolution of the mind. The brain division into the cybernetic and instinctive brain, the emergence of the memory and the foetal developmental split into intrauterine and extrauterine phase are connected respectively with appearance of the next levels of semiosis: organic semiosis (based on organic codes), interpretive semiosic (with the learning skills) and cultural semiosis (with language). The feelings in this theory plays an important role as a mean to establish the first-person experience and the intermediate step to consciousness.